THE MAIN DIALECTS OF THE UZBEK LANGUAGE AND THEIR REPRESENTATION IN WRITING - Panjiyeva Sevinch Xamza qizi (International Journal of Literature and Language Studies, 2026)
This article provides an in-depth historical, linguistic, and cultural analysis of the main dialects of the Uzbek language, the process of their formation, and their representation in written speech. The study examines the stages of development of Uzbek dialects, their geographical distribution, phonetic, lexical, and grammatical features, as well as their relationship with the literary language. The role of dialects in the formation of literary language norms, the use of dialectal units in fiction and oral folk literature, and the reasons for the limited application of dialects in written communication are discussed in detail. The research highlights the significance of studying dialects in the development of the Uzbek language and reveals their contribution to the progress of the national language.